Numerical investigations of natural convection in a square cavity-boundary conditions effects - Aswatha; Gangadhara Gowda, C.J.; Sridhara, N.; Seetharam, T.R.; Seetharamu, K.N. (Universiti Malaysia Perlis, 2009)
Organized by School of Mechatronic Engineering (UniMAP) & co-organized by The Institution of Engineering Malaysia (IEM), 11th - 13th October 2009 at Batu Feringhi, Penang, Malaysia.